Richards-Klute Equation on Graphs - Kolesnykov, Valerii (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2023)
This paper contains the formulation of the problem of mass transfer in a porous medium on a graph, on the edges of which the one-dimensional problem of mass transfer is modeled using the Richards-Klute equation. To combine separate Richards-Klute equations into a single system, auxiliary mass balance equations are introduced for the vertices of the graph. Problems of approximation of these equations at the vertices of the graph are also discussed.